Numerical simulation of an HTL-free carbon-based perovskite solar cell with graphitic carbon nitride doped zinc oxide as electron transport layers - Joseph Kariuki; Nicholas Rono; Chinedu Christian Ahia; Eric Kibagendi Osoro; Edson L. Meyer (Next Energy)
As a result of the advances in technology and the need for energy, an urge to develop a stable, high performance solar cell has initiated various scientific intentions to attain a cheaper and clean energy supply. In this work, a hole transport free (HTL-free) perovskite solar cell (PSC) with an architecture: FTO/ZnO-g-C3N4/CH3NH3PbI3/carbon was examined. The simulated device was validated with the already fabricated device in the literature. The electron transport layer (ETL) was a blend with ZnO and graphitic carbon nitride, and named GT1, GT3 and GT5 materials in different ratios. The band gap values of the proposed ETL were 3.06, 3.06, 3.10, and 2.97 eV for pure ZnO, GT1, GT3 and GT5 respectively. Simulations were carried out with an aid of a solar cell capacitance simulator (SCAPS-ID) conducted at AM 1.5 G and 100 mW cm−2. The optimal density defect of the absorber was maintained at 1.0×1012 cm−3, while the donor doping density of the ETL was achieved at 1.5×1022 cm−3 doping level. Utilization of palladium as the back contact led to achievement of a higher efficiency. The best device (with GT5 as ETL) achieved a decent power conversion efficiency of (PCE) of above 14%, a fill factor (FF) of 12.84%, a short circuit current density (Jsc) of 18.24 mA cm−2 and an open circuit voltage (Voc) of 6.04 V. The achieved PCE of above 14% was about 1.93% higher than the experimental value of PCE of 12.22%. Nonetheless, the proposed ETL materials were chosen by mimicking the actual experimental investigation with an aim of giving more insights theoretically. These results will help in further advancement and fabrication of the high performance HTL-free perovskite solar cells (PSCs) for anticipated commercialization.